Family Support Pattern for Treatment Adherence Among Tuberculosis Patients in Deli Serdang Regency : A Qualitative Study - Rahmad Gurusinga; Afrizal Afrizal; Adang Bachtiar; Firdawati Firdawati; Rizanda Machmud; Erlina Burhan; Jendrius Jendrius; Rima Semiarty (Jurnal Ilmu Kesehatan Masyarakat, 2024)
In Indonesia, 50% of tuberculosis (TB) treatments are discontinued prematurely. The success of TB treatment depends on patient adherence to completing the treatment. Family support is crucial in enhancing TB patient adherence, particularly regarding emotional and appreciation support. This study aims to explore the complexity of family support to TB patient adherence in Deli Serdang Regency, North Sumatra Province, Indonesia. This qualitative study employed participatory observation and in-depth interviews with TB patients and their family members. The research was conducted from February to April 2024 in Deli Serdang Regency, North Sumatra, Indonesia. Informants included 10 TB patients and 16 family members, selected purposively based on data from the public health center and the TB Program Holder. The researcher was the primary instrument of the study, focusing on two dimensions of family support: emotional and appreciation. Data validity was checked through credibility testing, including triangulation. The study findings indicate that family emotional support is reflected in expressions of empathy and caring. Sadness is evident from family members’ tears upon learning that a relative tested positive for TB. Family support is shown by accompanying TB patients to the health center and reminding them to take treatment. Appreciation support is demonstrated by valuing the patient’s treatment process. Family members encourage and motivate the patient to adhere to the treatment. Emotional and appreciation support from family plays a significant role in TB patient adherence to treatment. Families can significantly contribute to the success of TB treatment by demonstrating empathy, caring, and appreciation for the patient.